(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Iraqi insurance market need to develop products and to find new insurance policies to cover the damages of the violence and political commotions dangers and to meet the needs of the proposers. The global insurance companies recently issued such policies to pay the losses wich caused by the violent political acts of vandalism suffered by the property and investments wich estimated billions of dollars. All government institutions and private property in Iraq is not insured against the risk of political violence because there is no such an insurance form fit current events